Chemical composition of essential oil from the leaves of Cinnamomum camphora (L.) J. Presl - Cheribot Cherif, Maroua; Boughendjioua, Hicham; Sakhraoui, Nora (Journal of Phytology, 2024)
In the present study, the chemical composition of Cinnamomum camphora leaves collected from Algeria was studied. The chemical composition of the hydrodistilled essential oil of C. camphora, collected from Skikda (North Eastern Algeria), was analyzed by Gas Chromatography-Mass Spectrometry (GC-MS). The essential oil showed the presence of 17 major compounds representing 93.57% of total essential oil and the major compounds were camphor (36.81%), α-Pinene (9.91%), D-Limonene (8.63%) and Camphene (6.99%).